IMPROVING STUDENT LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING WITH THE ASSISTANCE OF INFOGRAPHICS ON HUMAN DIGESTIVE SYSTEM MATERIALS - Dyah Binti Astuti; Ridwan Joharmawan; Supriyanto Supriyanto (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2024)
Through the use of infographics and a problem-based learning approach, this research hopes to increase student understanding and engagement. This research was attended by eighteen female and sixteen male students in class VIII-B of SMP Negeri 1 Purwoasri for the 2023/2024 academic year. The Classroom Action Research (PTK) used is PTK with two learning cycles. There are four phases in an action research course: preparation, implementation, evaluation. Cognitive outcome tests and student learning response questionnaires were used to collect findings. The results of research using problem-based learning assisted by infographics achieved a percentage of completeness of cognitive learning outcomes from the pre-cycle of 26%, cycle I of 56%, and cycle II of 82%. The findings on the application of learning were also positive, namely 74.8 percent of cycle I students rated it as moderate, and 80.6 percent rated it as high. These findings suggest that combining problem-based learning with infographics for scientific education can improve learning outcomes and student responses.